Ijtihad Muhaimin Iskandar Tentang Usulan Penundaan Pemilu Dalam Wacana Kritik - Muhammad Asnan; Ferry Indra Sukma; Zulfikri Nurfadhila (Sahafa Journal of Islamic Communication, 2023)
The purpose of this study is to find out how the critical discourse analysis of Kompas.com and Republika.co.id in reporting on the proposed postponement of the election which was rolled out by Muhaimin Iskandar as a political ijtihad. Using a qualitative approach with the critical discourse analysis method of the Van Dijk Model, several theories in research place Image Theory, Ijtihad Theory as supporting theories for the main theory. The results of the study show how each media in March equally objectively discussed themes related to the proposed postponement of the elections initiated by Muhaimin Iskandar and several political party leaders. This conclusion is reinforced by the macro structure, super structure, and macro structure which mutually reinforce the theme. The situation was different when the phenomenon of rejection began to emerge towards the idea of postponing the elections in April 2022. Even though the discourse that was presented seemed to be the same, if observed in detail there were differences that emerged between the two media. Kompas.com at this moment still tends to be objective in discussing Muhaimin's mature attitude, which seems not to insist on continuing his idea. Republika.co.id presents different discourse concepts through macro-structure, super-structure and micro-structure which tend to be unfavorable to Muhaimin's position, one of which is because he makes joke-like quotes as headlines. In the perspective of ijtihad in the field of self-image politics, what Muhaimin Iskandar has done through the proposed postponement of the 2024 elections can be called the seriousness of the parties concerned to build their own image.